2014
DOI: 10.1016/s1995-7645(14)60198-x
|View full text |Cite
|
Sign up to set email alerts
|

The most common herbal medicines affecting Sarcomastigophora branches: a review study

Abstract: Parasitic diseases cause annual mortality of more than 200 thousand people. Currently many drugs are used to treat parasitic diseases; however, they are mostly expensive, toxic, with side effects and drug resistance. Medicinal plants have been shown to represent natural source of cheap drugs with low toxicity. In this review article, the most common and most effective herbal medicines on pathogenic protozoan Sarcomastigophora branches such as Trypanosoma, Leishmania, Amoeba, Trichomonas and Giardia were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Furthermore, medicinal herbs are also effective in prevention and treatment of the toxicity induced by other drugs or toxins [30][31][32][33][34][35][36][37] . Medicinal plants are a rich source of bioactive substances, antioxidants, flavonoids, and phenolic substances and have multiple health effects [12,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, medicinal herbs are also effective in prevention and treatment of the toxicity induced by other drugs or toxins [30][31][32][33][34][35][36][37] . Medicinal plants are a rich source of bioactive substances, antioxidants, flavonoids, and phenolic substances and have multiple health effects [12,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Although soy and its isoflavones can cause harmful effects in some conditions, animal studies have suggested that soy has no toxic effect. 18 Clinical studies suggest that soy decreases the level of the testosterone hormone in men. Moreover, some studies indicate the presence of estrogenic property in soy isoflavones.…”
Section: Lipid-lowering Medicinal Plantsmentioning
confidence: 99%
“…13,14 Fortunately, extensive studies have been done on the effectiveness of medicinal plants used in traditional medicine over the 30 past years and some of their efficiencies and deficiency have been recorded. [15][16][17][18] This review was therefore aimed to introduce some promising medicinal plants effective in the prevention or treatment of hyperlipidemia, apart from presenting the possibility of their intoxication and drug interaction.…”
mentioning
confidence: 99%
“…Another secondary metabolite isolated from Chenopodium ambrosioides called as Ascoridole is known for their anti-ascariasis properties (Romero-Benavides et al 2017). Several other herbal plants have been used in control and elimination of intestinal worms like Ricinus communis, Juglans nigra, Artemisia vulgaris, Matricaria chamomilla, Dryopteris filixmas, Syzygium aromaticum (Bahmani et al 2014). It has been seen that the active constituents of plants having therapeutic properties are mostly products of secondary metabolic pathways such as shikimate, phenyl-propanoid pathway, acetate-mevalonate and glucosinolate pathways to name a few.…”
Section: Introductionmentioning
confidence: 99%